Clinical, Demographic Characteristics and Factors Affecting the Clinical Outcome of Children with Electrical Injury: A Single-Center Pediatric Emergency Clinic Experience - Berksoy, Emel Ataş; Yazıcı, Selçuk (The Bulletin of Legal Medicine, 2019)
Objective: The aim of this study was to determine the demographic and clinical characteristics of childhood electrical injuries and to determine the factors affecting clinical outcome.Materials and Methods:The data of 112 patients who applied to the emergency department between January 2008 and December 2015 were retrospectively analyzed. The patients were divided into three groups as under 6 years of age, 6 to 10 years old and 10 years of age and over, and the relationship between the groups in terms of electricity supply and voltage, the occurrence of injury, clinical complaints and laboratory values were examined.Results:  78 (69.6%) of the patients were male and 34 (30.4%) were female. The median age was 5 years (11 months-15 years). 101 of the patients (90.2%) had injured with low-voltage current and 88 (78.6%) were injured in the house environment. According to the electrical source, the most frequent causes of injury were plug sockets under the age of six years (67.9%), electrical cable between the ages of six to ten years (39.4%), electrical devices over ten years of age (41.6%). Two patients had sinus bradycardia and four patients had soft tissue trauma due to fall.None of the patients had deep tissue damage, severe burn and renal failure. Troponin I, liver and kidney function tests, serum electrolytes, leukocyte levels were normal in all patients.Conclusion: The majority of electrical injuries in children were due to low voltage current and preventable household contact. Further investigations may not be required in low-voltage electrical injuries with ...
Keywords: electrical injury; child; trauma